TIGA MEKANISME KEPATUHAN HUKUM DALAM KONTEKS REGULASI FIFA: KAJIAN SOSIOLOGI HUKUM - Abdusyahid Naufal Fathullah Fathullah (Realism: Law Review, 2024)
Supranational regulatory bodies (SRB) are bodies that have the authority to make and enforce regulations that apply in various countries, in this case FIFA as the parent football organization that runs cross-country regulations and each member is obliged to comply with them. The importance of this paper is to review how legal compliance from three legal compliance mechanisms in Suprantional Regulatory Bodies. By using sociolegal methods and describing them across disciplines so that it was found that FIFA can encourage countries to solve legal problems in sports which are certainly in accordance with the policies of each country.